Karakteristik Sate Padang dalam Kemasan dengan Suhu dan Waktu Simpan Berbeda - Panji Khairi Putra; Tuti Suryati; Zakiah Wulandari (Jurnal Ilmu Pertanian Indonesia, 2024)
Padang satay is a typical West Sumatran food that is part of Indonesia's traditional heritage. The experiment was carried out to overcome the problem of decreasing the quality of padang satay products. The vacuum and sterilization method utilized retort pouch packaging, which was anticipated to preserve product quality for up to 21 days during storage at both room and cold temperatures. This study aims to assess the effectiveness of retort pouch packaging in maintaining the quality of satay products by examining their physical, chemical, and microbiological properties after being packaged in retort pouches and stored for 21 days. The research employed a completely randomized design with a factorial arrangement of 2 factors and 4 replications.. Replications were taken for each temperature and storage time. The results showed a significant interaction between cold temperature treatment and storage for up to 21 days, maintaining pH values, water activity, and microbiological quality. Furthermore, the interaction between room temperature and cold temperature treatment could not significantly affect antioxidant activity and MDA levels (p<0.05). In conclusion, padang satay packaging using retort pouch could improve and maintain physicochemical quality in pH, water activity, and microbiology. However, it could not increase antioxidant activity or reduce the MDA level of the product. Keywords: packaging, retort pouch, satay padang, temperature storage